Proposta de jornalismo público da TV Cultura: o que há de novo nas pautas e produção do telejornal? - Garcia, Maria Tereza (2011)
This paper presents the proposal of public journalism implanted by TV Cultura, and the mishaps encountered in this decade of implementation. In spite of the creation of public journalism celebrating two decades in the United States, the concept is ignored and disbelieved for some. The public journalism, which emerged as a movement by American journalists, was focused on the reunion of journalism with democratic principles and ethics in all the news production, and not necessarily proposing a new format or a new category of journalism. Act that way, however, requires more than just good intentions or good will, since the journalistic output was hampered by diverse interests of the company that manages it. Thus, the study conducted here takes into account the political and economic contexts in which public journalism was practiced, as well as professional and technological conditions for its development, using for this, the concepts discussed in the theories of journalism and agenda-setting newsmaking